2018
DOI: 10.3390/nu10091200
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast in the United States: Food and Nutrient Intakes in Relation to Diet Quality in National Health and Examination Survey 2011–2014. A Study from the International Breakfast Research Initiative

Abstract: The contribution of breakfast to diet quality (DQ) can inform future dietary guidelines. This study examined breakfast nutrition in relation to overall DQ, using dietary data from the first reported day of the National Health and Examination Survey (NHANES) 2011–2014 (n = 14,488). Relative DQ was assessed using the Nutrient Rich Foods Index (NRF9.3) and the USDA Healthy Eating Index 2015 (HEI 2015). The sample was stratified by NRF9.3 tertiles and by age and socioeconomic groups. Four out of 5 NHANES participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 37 publications
11
88
2
2
Order By: Relevance
“…In the present study, the rate of breakfast skipping among female students was 17·2 %; this result is in agreement with those published from other countries including the USA (18·0 %) (39) , UK (19·9 %) (21) and Belgium (16·9 %) (22) . However, the rate of breakfast skipping in the present study was inconsistent with the rate previously reported for Japanese adolescents (2·3 %) (23) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the rate of breakfast skipping among female students was 17·2 %; this result is in agreement with those published from other countries including the USA (18·0 %) (39) , UK (19·9 %) (21) and Belgium (16·9 %) (22) . However, the rate of breakfast skipping in the present study was inconsistent with the rate previously reported for Japanese adolescents (2·3 %) (23) .…”
Section: Discussionsupporting
confidence: 93%
“…The habitual intakes of vitamin B 6 , folate and Mg were higher among breakfast consumers than among breakfast skippers, which was consistent with the result that the contribution of vitamin B 6 , folate and Mg intakes at breakfast was reported to be approximately 20 % of total intake of these nutrients (39) . However, the nutrient intake adequacy of vitamin B 6 , folate and Mg intakes was not different between the two groups both in crude model and adjusted model analyses.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we used the Healthy Eating Index 2015 (HEI-2015) [32][33][34] and Nutrient-Rich Food Index 9.3 (NRF9.3) [35][36][37][38] as measures of diet quality. The HEI-2015 is a 100 point scale to assess compliance with the 2015-2020 Dietary Guidelines for Americans [39], with a higher score indicating a better quality of overall diet.…”
Section: Calculation Of Diet Quality Scoresmentioning
confidence: 99%
“…We conducted a feasibility analysis to ascertain if we could detect a difference in nutritional density of school foods in children's 24-hour dietary recalls. We used a peer-reviewed method (41,42) to calculated the nutrient density of school-aged children's weekday lunches in NHANES 2009-2016 dietary recalls. We used survey regression to compare changes in nutrient density of lunches from school cafeterias versus any other source.…”
Section: Feasibility and Sensitivity Analysesmentioning
confidence: 99%